The Association Between African American Father–Child Relationships and HIV Testing - Boyd, Donte T. (Am J Mens Health, 2020)
The existing literature identifies parent communication as a protective mechanism in the reduction of sexual risk behaviors among youth; however, not much is known about father–child communication and bonding and its association with HIV testing. Therefore, this study examines the link between the relationship, bonding, and communication shared by African American (AA) fathers and their children and HIV testing over time. This secondary data analysis included data from Waves 1 and 3 of the National Longitudinal Study of Adolescent to Adult Health on the health of adolescents to adults in a sample of AA males and females (N = 509), with a mean age of 16 years. The independent variables included fathers’ communication, bonding, and relationships, and the dependent variables included HIV testing. A multinomial analysis assessed the factors that contributed to or prevented HIV testing. It was found that the overall model was statistically significant; F(24, 55) = 8.95; p < .001. The results suggest that father–adolescent communication was statistically significant and positively associated with HIV testing (B = 23.88; p < .05). AA adolescents who reported going to the doctor or making a nursing visit were more likely to get tested multiple times (B = 13.91; p < .001). Our findings indicate that father–child relationships are essential to adolescent sexual development and serve as a protective factor against threats to sexual health. Future studies should be designed to investigate the cognitive mechanisms through which the father–child bonding and communication may impact HIV testing.